Single-session upper limb plyometric training is as effective as two sessions for improving muscle strength, power, and serve velocity in male youth tennis players: a randomized parallel controlled study - Wang, Jian; Xu, Qi (Frontiers in Psychology, 2025)
IntroductionProviding a balanced training stimulus that promotes positive adaptations without excessively increasing training volume—and thereby avoiding disruptions to the training process—is a challenging task for strength and conditioning coaches. This study aimed to compare the effects of one vs. two weekly sessions of upper limb plyometric training (ULPT) on muscle strength, power, and serve velocity in male youth tennis players.MethodsWe conducted a randomized controlled study with two ULPT groups: one receiving one session weekly (ULPT1w) and the other two sessions (ULPT2w), alongside a control group maintaining regular tennis training. The intervention lasted 8 weeks. A total of 47 male youth tennis players (15.6 ± 0.9 years), competing at the trained/developmental level, participated in the study. Evaluations were conducted twice—once before the intervention and once after—assessing isometric shoulder rotation strength (internal [ISRT] and external [ESRT]) with a dynamometer, the medicine ball chest throw (MBCT), seated shot-put test (SST), and serve velocity using a radar gun.ResultsIn the post-intervention, significant differences were observed between groups for the variables of ISRT (p = 0.010; ηp2 = 0.189), ESRT (p = 0.004; ηp2 = 0.226), MBCT (p = 0.012; ηp2 = 0.181), SST (p = 0.019; ηp2 = 0.164), and tennis serve velocity (p = 0.004; ηp2 = 0.226).ConclusionThe study found that ULPT significantly improves upper limb muscle strength, power, and serve velocity in young male tennis players, with both once and twice weekly training yielding similar benefits. As practical implications coaches can effectively incorporate ULPT once a week to enhance physical performance in young male tennis players.